A successful bronchial thermoplasty procedure in a "very severe" asthma patient with rare complications: a case report. (2nd September 2019) - Han, Xiudi; Zhang, Shuli; Zhao, Weiye; Wei, Dong; Wang, Yi; Hogarth, Douglas Kyle; Liu, Xuedong
Abstract: Introduction : Bronchial thermoplasty (BT) is a unique bronchoscopic treatment for severe asthma that utilizes radiofrequency ablation to reduce smooth muscle in the bronchial walls. Current studies mainly focused on uncontrolled severe asthma with a forced expiratory volume in 1 second (FEV1 ) above 60% and associated complications, no human studies have performed on "very severe" asthma as well as its complications. Case study : We present a 60-year-old male with more than 15 years history of very severe asthma, who underwent BT. His FEV1 was only 20.4% predicted, which would have excluded him from all prior clinical trials of BT. The first BT procedure occurred without an issue. After the second BT procedure, he experienced severe dyspnea due to an infection with a non-flu respiratory virus. This illness was complicated by the formation of a pulmonary cyst. During recovering from the third procedure, he developed stomach stones. This is mainly related with taking large amounts of hawthorn previously, also cannot exclude the role of thermal energy injury on gastrointestinal nerve function. Results : Despite these unexpected complications, his quality of life greatly improved after BT, yet his lung function did not improve. Conclusion : This case is the first to describe BT procedures in patient with this level of lung function compromise, although accompanied with rare complications; our report indicates BT may be an opportunity and choice for the "very severe" asthma patients.